Market crashes as critical phenomena? Explanation, idealization, and universality in econophysics. - Jhun, Jennifer; Palacios, Patricia; Weatherall, James Owen (Synthese, 2018)
We study the Johansen-Ledoit-Sornette (JLS) model of financial market crashes (Johansen et al. in Int J Theor Appl Financ 3(2):219-255, 2000). On our view, the JLS model is a curious case from the perspective of the recent philosophy of science literature, as it is naturally construed as a “minimal model” in the sense of Batterman and Rice (Philos Sci 81(3):349-376, 2014) that nonetheless provides a causal explanation of market crashes, in the sense of Woodward’s interventionist account of causation (Woodward in Making things happen: a theory of causal explanation. Oxford University Press, Oxford, 2003).